Impact of Venture Capital on Startup Success and Economic Growth in Nepal - Bhandari, Indra Bahadur (Nepalese Journal of Finance, 2025)
This study examines the impact of venture capital on startup success and economic growth. Startup success and economic growth are the dependent variables. The selected independent variables are Venture capital, access to capital, networking, innovation & technology, government policies & regulations and market conditions. The study is based on primary data of 120 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of venture capital, access to capital, networking, innovation & technology, government policies & regulations and market condition on economic growth and startup success. The study showed a positive impact of venture capital on startup success and economic growth. It indicates that increase in venture capital leads to increase in startup success and economic growth. Likewise, access to capital has a positive impact on the startup success and economic growth. It indicates that increase in access to capital leads to increase in startup success and economic growth. Similarly, networking has a positive impact on startup success and economic growth. It indicates that increase in networking leads to increase in startup success and economic growth. The study also indicates that market condition has a positive impact on startup success and economic growth. It indicates that increase in market condition leads to increase in startup success and economic growth. Moreover, innovation and technology have a positive impact on startup success and economic growth. It indicates that increase in innovation and technology leads to the increase in startup success and economic growth. Furthermore, government policies and regulations has a positive impact on the startup success and economic growth. It indicates that increase in government policies and regulations leads to the increase in startup success and economic growth.